Magnetic hybrid imprinted polymers with three-templates modified by DESs for the rapid purification of monosaccharide from seaweed. Issue 20 (14th December 2017) - Li, Guizhen; Row, Kyung Ho
ABSTRACT: Fe3 O4 @hybrid-molecular-imprinted polymers (Fe3 O4 @HMIPs) with three monosaccharide templates (D -(+)-galactose, L -(−)-fucose, andD -(+)-mannose), and hybrid materials were modified by deep eutectic solvents (DESs). The materials obtained were combined with solid-phase extraction (SPE) to purify ofD -(+)-galactose, L -(−)-fucose, andD -(+)-mannose from seaweed, and the SPE procedure was optimized further. Compared to Fe3 O4 @HMIPs, DESs-Fe3 O4 @HMIPs were developed to achieve stronger recognition and higher recoveries ofD -(+)-galactose, L -(−)-fucose, andD -(+)-mannose from seaweed . The optimal practical recoveries of the three monosaccharides, D -(+)-galactose, L -(−)-fucose, andD -(+)-mannose, purified by DESs-4-Fe3 O4 @HMIPs from seaweed were 90.12, 92.82, and 91.94%, respectively. When acetone was used as the washing solution, the actual amounts extracted were 6.87, 4.17, and 5.29 mg · g −1, respectively. GRAPHICAL ABSTRACT: